1980
DOI: 10.1095/biolreprod23.3.621
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships Between Follicular Fluid Steroid Levels, GonadotropiC Stimuli, and Oocyte Maturation During Preovulatory Development of Porcine Follicles1

Abstract: Prepubertal gifts were treated with 750 IU pregnant mare serum gonadotropin (PMSG) and 72 h later with 500 IU human chonionic gonadotropin (hCG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
80
2

Year Published

1982
1982
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 0 publications
9
80
2
Order By: Relevance
“…Our follicle diameter and steroid levels in FF agree quite well with recently published data with well-defined porcine material (Corbin et al 2003) or earlier data (Ainsworth et al 1980, Babalola & Shapiro 1988, Grant et al 1989. The periovulatory group is defined and selected by the very high ascent of PGF2a level in FF.…”
Section: Follicle Groupsupporting
confidence: 89%
“…Our follicle diameter and steroid levels in FF agree quite well with recently published data with well-defined porcine material (Corbin et al 2003) or earlier data (Ainsworth et al 1980, Babalola & Shapiro 1988, Grant et al 1989. The periovulatory group is defined and selected by the very high ascent of PGF2a level in FF.…”
Section: Follicle Groupsupporting
confidence: 89%
“…This result is comparable to those of Ainsworth et al (1980;P 4 : 901 ± 208 ng/ml, E 2 : 14.4 ± 1.6 pg/ml) and Blödow et al (1990;P 4 : 675.1 ± 135.4 ng/ml, E 2 : 20.8 ± 14.2 pg/ml). Regardless of whether they are from PMSG/hCG-primed or spontaneously ovulating gilts, late preovulatory follicles have a higher progesterone/oestradiol-17β ratio (Ainsworth et al, 1980;Blödow et al, 1990;Guthrie et al, 1993;Conley et al, 1994). This is due to the dramatic decrease of follicular capacity to produce oestradiol-17β, and the increased progesterone production after preovulatory LH surge or hCG administration (Downey and Driancourt, 1994).…”
Section: Discussionsupporting
confidence: 89%
“…It has been demonstrated that follicles are heterogeneous both in spontaneously ovulating and PMSG/hCG-primed gilts and sows. Morphological and biochemical asynchrony continues into the immediate preovulatory period and follicles respond differently to the LH/hCG surge signal, reflecting their maturational status at that time (Ainsworth et al, 1980;Grant, 1989;Hunter et al, 1989;Hunter and Wiesak, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of PGE 2 in FF were observed to peak at around 36 h post-hCG in the follicle (Tsang et al 1979). An inverse relationship of progesterone to oestrogen was observed at the time of PGE 2 peak (Ainsworth et al 1980) and the theca cells were found to be the predominant follicular source of PGE 2 compared to the granulosa cells (Evans et al 1983). These observations, together with our previous finding of upregulation of endometrial COX-2 by SP, support the proposal that uterine-derived PGE 2 may be the active intermediary in accelerating the follicular events, which culminate in ovulation followed by corpus luteum development.…”
Section: S O'leary and Othersmentioning
confidence: 95%
“…The role of prostaglandins in preovulatory follicular function has been described in prepubertal gilts synchronised with eCG and hCG (Tsang et al 1979, Ainsworth et al 1980, Evans et al 1983. Levels of PGE 2 in FF were observed to peak at around 36 h post-hCG in the follicle (Tsang et al 1979).…”
Section: S O'leary and Othersmentioning
confidence: 99%